"I Want That Life a Lot…How on Earth Do I Get That?" Examining Challenges for Men With Barth Syndrome in Their Transitions to Adulthood. (November 2021) - Mazar, Iyar; Moorman, Sara M.
VFor youth with life-limiting chronic illnesses, transitioning to adulthood in line with age-norms may be difficult due to symptom severity and shortened survival. This study explores whether individuals with Barth syndrome (BTHS), a condition uniquely characterized by extreme prognostic uncertainty, experience similar or different challenges compared to youth with other conditions. During focus groups with adults with BTHS ( n = 12) and caregivers ( n = 13), participants reported that the ability to independently manage one's health condition, the social/emotional impacts of BTHS, and the ability to set goals in the context of future uncertainty challenge their transition to adulthood. This aligns with prior research, indicating that prognostic uncertainty may hinder long-term goal setting in BTHS. Implications of these findings include providing strategies for identifying meaningful alternative goals for individuals with chronic illnesses to target, promoting increased autonomy earlier in youth, and fostering coping strategies to manage non-disease related impacts.